ปัจจัยที่มีความเสี่ยงต่อการตกเป็นเหยื่ออาชญากรรมทางเพศของผู้หญิงไทย : รายงานผลการวิจัย - จุฑารัตน์ เอื้ออำนวย (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research is a field research that used both Social Science and Anthropological Methods. Interview questionnaires were used to collect data from the sex crime offenders of 444 cases in 12 provincial corrections and used in-depth interview to collect the life history of 10 sex offenders and 7 victims. The objectives of the research are: to analyze the risking characteristics, relation, place, time and situation for rape and to find the measurement to prevent rape in the Thai society . The results of the research can be summarized as follows: Social: Most of the sex offenders are single, low economic and social status, low education, lack of sexology knowledge, and lack of commitment in their role and duty as father, uncle of the girl and society. Culture: Learning patriarchal sub-culture and used the power behind masculine to del. Unfair to female as male’s asset that can buy and share to their friends Behavior: There are flaws in socialization to be "self" of the sex offenders, could not control their sex drives, could not bare the temptation, promiscuity, and used alcohol and narcotics before rape. Mind: Hyper-sexual gratification, low shameless and lack of victim identification mind. In conclusion, factors risking to be rape victims for Thai female are debut, ages 11-15, be students, raped by their boyfriends, friend and neighbor at sex offenders’ houses and also the houses of their friends, during 22.01 pm.-02.00 am. Sex crime victim’s figures in the offender’s visions are: good looking shape, naked suit and careless.